Fetal arrhythmias case series: Experiences from a fetal screening center in Taiwan - Wan-Ling Chih; Ksenia Olisova; Yu-Hsuan Tung; Yi-Ling Huang; Tung-Yao Chang (Elsevier, 2023)
Objective: Fetal arrhythmias are common and in rare cases can be associated with severe mortality and morbidity. Most existing articles are focused on classification of fetal arrhythmias in referral centers. Our main objective was to analyze types, clinical characteristics, and outcomes for arrhythmia cases in general practice. Case report: We retrospectively reviewed a case series of fetal arrhythmias in a fetal medicine clinic between September 2017 and August 2021. Fetal arrhythmias in our sample presented by: Ectopies (86%, n = 57), bradyarrhythmias (11%, n = 7), and tachyarrhythmias (3%, n = 2). One tachyarrhythmia case was associated with Ebstein's anomaly. Two cases of second-degree AV block received transplacental fluorinated steroid therapy with recovery of fetal cardiac rhythm in later gestation. One case of complete AV block developed hydrops fetalis. Conclusion: Detection and careful stratification of fetal arrhythmias in obstetric screening is crucial. While most arrhythmias are benign and self-limited, some require prompt referral and timely intervention.